Pembinaan Kompetensi Mengajar Bahasa Arab Berbasis European Profiling Grid - Arifah, Fatwa (Al-Ma‘rifah, 2021)
This study aims to compile a syllabus of the European Profiling Grid (EPG) based teaching competency development course to improve the teaching competence of students to become Arabic teachers with character and competitiveness. The method used in this study is a research and development approach by Richey and Klein’s model with the steps of planning, production, and evaluation. This study identified that some of the EPG aspects had been contained in several other subjects, such as Planning of Arabic Learning, Methodology of Arabic Learning, and Learning Media Arabic. However, there are still several aspects of the EPG that have not yet become a concern in several courses, such as intercultural competence. Thus, several aspects of the EPG such as intercultural competence, professional behavior, administration need to be integrated as a syllabus model for the EPG-based Arabic teaching competence development. The EPG-based teaching competency development syllabus needs to be accompanied by appropriate teaching materials and research instruments. Therefore, research on the development of the next model needs to be done so that the development of teaching competency syllabus based on the EPG can be applied in learning.